Evaluation to Identify Benzene Safe Concentration in Oil and Gas processing Facility in East Java Area Due to Process Fugitive Emission - Ahmad Muslih Bambang Sugiharta1, Aditya1, Abdul Rohim Tualeka2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Benzene is an organic chemical compound with the chemical formula C6H6. The benzene molecule is composed of six carbon atoms joined in a ring with one hydrogen atom attached to each. Acute benzene exposure can cause central nervous system depression. Longterm exposure can result in depression of the blood-forming system and may increase risks associated with anemia and leukemia. The purpose of this research is to identify benzene safe concentration in crude oil processing plant in east java area due to process fugitive emission. Sample is taken from 20 workers include work duration and weight of the worker also crude oil plant air quality monitoring is measured using direct-measure benzene detectors.In the benzene measurement on the crude oil plant in east java area, 2 spot sample is taken with resulting data 0.96 mg/m3 or 0.30 ppm and 0.86 mg/m3 or 0.27 ppm, and according to final manual calculation for safe benzene concentration with the result 1.12 mg/m3 or 0.35 ppm, all of those number are still below safe concentration limit by refer to minister of man power No.13 / MEN / X / 2011 regulation and The Occupational Exposure Limits (OELs) which have been adopted globally as a company standard which is 0.5 ppm as an eight hour time-weighted average (TWA8) and 1.0 ppm as a Short Term Exposure Limit (STEL) (averaged over fifteen minutes). But according to Minimum Risk Level (MRL) ATSDR 2007, those value already above threshold which is 0,009 ppm daily exposure for acute effect and 0,003 ppm daily exposure for chronic effect, Recommendation to control and reduce fugitive emission which resulting in number of benzene is by reviewing engineering design for equipment causing fugitive emission, and since this company regulation for respirator usage in benzene case are 0.5-5.0 ppm must use Half-face mask with organic vapor cartridge, 5.0-25.0 ppm use Full-face mask with organic vapor cartridge, and Greater than 25 ppm use Self-Contained Breathing Air (SCBA) then need to re asses all area which has an obligation to wear personal protective equipment (Half-full / full mask with organic vapor cartridge or Self contain breathing apparatus) by not only based on benzene level but also considering the exposure duration. .